Developing an Interactive Audiovisual Media for Listening Assessment - Wiyanah, Sri; Setiawan, Agung Yoga (Journal of English Language Teaching and English Linguistics, 2026)
This study aims to overcome the limitations of traditional listening tests by designing and developing an interactive audiovisual evaluation tool to enhance listening assessment in higher education. The tool integrates interactive features and varied audiovisual content to provide a more dynamic and engaging assessment experience. The research focused on second-semester students of the Listening and Speaking for Formal Communication course in the English Education Department at Universitas PGRI Yogyakarta. The Research and Development (R&D) approach was implemented using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through lecturer interviews, student questionnaires, expert validations, classroom observations, and student feedback. The final product, developed using Microsoft PowerPoint, included a Home menu, Test Information, and three listening test sections tailored to students’ learning needs. The Results indicate that each ADDIE stage contributed to the successful development of the audiovisual-based assessment tool. The prototype addressed limitations of conventional listening tests and proved effective during implementation, as students performed better and responded positively. Expert and learner evaluations confirmed its feasibility and practical in use. The findings demonstrate that multimedia-integrated assessment enhances authenticity, motivation, and comprehension in listening learning, while offering opportunities for future expansion to web- or mobile-based platforms. Keywords: Assessment, Audiovisual, Interactive, Listening, Research and development